(untitled) (Jurnal Bahasa, 2018)
Malay proverb is one of the evidence that reflects the high level of wisdom and reasoning of the Malay mind. Proverbs normally have exact, concise and complex meanings. Their meanings cannot be understood literally. This happens because the Malay proverb has both concrete and abstract meaning that can be mapped through the domain and target source. This article aims to explain the process that occurs in the mind as well as to explain the reasoning and philosophy why certain objects are chosen as an object to a proverb. 31 Malay proverbs using the lexical item "garam" (salt) is generated from the website (http://www.malayciviliza ion.com.my/peribahasa) This study employs the inquisitive semantics framework proposed by Nor Hashimah (2014). The combination of corpus data, theory, philosophy, and culture proves its effectiveness in exploring the reasoning and wisdom of the Malay mind. Findings reveal that there are several features that serve as a mechanism in abstracting the concrete meaning. "Garam" is abstracted by a feature [+cheap] as well as "easy to melt" to reflect the meaning of "despicable". "Garam" is also abstracted as a "despicable person" by the Malays because of its "easy to dissolve" property. Through this research, the abstraction that happens in proverbs are able to be described and simultaneously reflect the wisdom of the Malay mind. Keywords: Malay proverbs, abstraction, Malay cognitive reasoning, Malay mind, inquisitive semantics framework